Evaluation Implementation Project With Use Earned Value Method ( Object Case : Construction Project of the IAIN Lhoksemawe Laboratory Center Building ) - Gofirli Saumah Saumah; M Fauzan; Nura Usrina; T Mudi Hafli; Syibral Malasyi; David Sarana; Muhammad Muhammad (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
This study applies EVM to the IAIN Lhokseumawe Laboratory Center Building Construction Project to evaluate its cost and schedule performance. The primary objective of the study is to assess how well the project adheres to its planned budget and timeline. Data was collected from project documents over the first 24 weeks, including progress reports and cost records. Key performance indicators (KPIs) such as Schedule Variance (SV), Schedule Performance Index (SPI), Cost Variance (CV), and Cost Performance Index (CPI) were calculated. The results show that by the 24th week, the Schedule Variance (SV) is Rp 0 and the SPI is 1, indicating that the project is on schedule. Regarding cost, from Week 1 to Week 21, the project has incurred costs lower than planned, with a positive Cost Variance (CV) of Rp 12,927,390,000, and a Cost Performance Index (CPI) greater than 1 (1.11), indicating strong cost control and efficiency. Overall, the project is progressing as planned with excellent cost and time performance. The findings suggest that EVM is an effective tool for monitoring and controlling construction projects.